What Counts as Progress? The Contradictions of Global Health Initiatives. Issue 1 (2nd January 2016) - Roalkvam, Sidsel; McNeill, Desmond
Abstract : Global initiatives to finance maternal and child health have saved millions of lives and protected millions more against the ravages of crippling and debilitating disease; for this they are to be highly commended. Such technological and vertical programmes are appealing to policy-makers at the global level; but these health interventions take place within complex social and economic structures, and pertinent questions have been raised both about some negative consequences of these programmes and the implications for governance at local, national and global levels. Based on recent and ongoing research, and especially on a case study from India, this article critically assesses these related concerns. Is it the case that these programmes may actually weaken local health systems, which are crucial both in themselves and for ensuring health improvements? Do they change the direction of accountability, with national governments becoming accountable upwards to donors (for achieving specified numerical targets) rather than downwards to their citizens? And do such programmes also serve to de-politicize the field of global public health, diverting attention from the responsibilities of powerful nations to rectify the shortcomings of the global political economy and global governance which impact negatively on people's health?